The Effect Of The REACT Strategy On The Achievement Of Arabic Grammar Among Fourth-Grade Science Students (Journal of the College of Basic Education, 2025)
The research aims to identify the effect of the REACT strategy on the achievement of Arabic grammar among fourth-grade science students by verifying the validity of the following null hypothesis (There is no statistically significant difference at a significance level of (0.05) between the average scores of students in the experimental group who study Arabic grammar using the REACT strategy and the average scores of students in the control group who study in the usual way in the post-achievement test prepared by the researcher). The researcher adopted the experimental design with partial control for the two research groups. The experimental and control research groups were subjected to the post-test. The researcher chose the morning preparatory and secondary schools in Diyala Governorate as a community for his research. The research sample amounted to (60) students, with (30) students for the experimental group and (30) students for the control group. The results showed that the experimental group outperformed the control group in the post-achievement test in Arabic grammar.